Crimes of Assaulting Privacy and Violating Public Morals via Smart Phones. According to the Information Technology Crime Law and the Telecommunications Regulatory Law; A comparative Analytical Study. - Al-Sheyyab, Tayel Mahmoud; Abu Bakir, Mohammed Khalil Yusuf (International Journal of Psychosocial Rehabilitation, 2020)
The present study is concerned with the issue of crimes of assaulting privacy and violating public morals via smart phones according to the Information Technology Crime Law and the UAE Telecommunications Regulatory Law in comparison to the Jordanian legislation. The present study deals with the topic by clarifying the concept of smart phones and crimes committed via smart phones and the information network. The study shows how the UAE and Jordanian legislators handle these crimes according to the law of combating information technology crimes and the law of regulating the communications sector. The present study also clarifies the right of the aggrieved party to claim compensation Due to these crimes being committed. It is noticed that there is a slight difference between the UAE and Jordanian legislations, which is shown in the results and recommendations.